Associations between the spiritual well-being (EORTC QLQ-SWB32) and quality of life (EORTC QLQ-C30) of patients receiving palliative care for cancer in Cyprus - Kyranou, Maria; Nicolaou, Marianna (My University, 2021)
Background: Spiritual well-being is increasingly investigated in relation to patients’ perceived quality of life and is generally thought as having the potential to support patients with cancer who receive palliative care. Until recently, questionnaires used to assess spiritual well-being were developed mainly in the US. The purpose of this study was to translate and use the EORTC- SWB32, a newly developed tool, validated recently in 4 continents, 14 countries, and in 10 languages, to explore relationships of spiritual well-being with quality of life in patients with cancer. Methods: One hundred four patients participated in this study with an average age of 59 years. Of those, 79% were dealing with metastatic cancer. Data collection took place in three oncology centers from two large cities in Cyprus. The acceptability of the translated items was tested. Two questionnaires were employed for the assessment of quality of life and spiritual well-being, developed by the same organization: the EORTC QLQ-C30 and the EORTC QLQ-SWB32. The scores for each tool were analyzed separately and correlations between the two measures were explored. Results: Patients found the items of the SWB32 tool easy to understand and answer. They attested that filling the questionnaire prompted thoughts about their own spirituality. The mean score for Global Spiritual Well-Being was 60.4 (SD = 23.7) and it was associated with the mean scores in the scales “Emotional functioning” and “Cognitive functioning” of the EORTC-QOL-C30 (0.42 and 0.40 respectively, p < 0.01). The mean score for the “Relationship with God” scale (74.9, SD = 29.7) reported by the Cypriot patients is high and compatible with the homogenous spiritual orientation of the island’s population. Conclusions: All subscales of the SWB32 tool demonstrated good internal consistency in this study. Significant associations were observed between dimensions of quality of life and spiritual well-being. Additionally, the participants found the items easy to answer consistent with the tool’s suggested clinical utility which lays the ground for the application of targeted interventions to enhance spiritual well-being.
Keywords: Cancer; Palliative care; Quality of life; Spiritual well-being